Pengaruh Pupuk Organik dan Plant Growth Promoting Rhizobacteria terhadap Pertumbuhan dan Hasil Kedelai - Fajar Setyawan; M. Machfud Aldi; Abu Talkah (Perkumpulan Agroteknologi/Agroekoteknologi Indonesia, 2021)
Nutrient availability is very significant in supporting plant growth. The low content of organic fertilizers and existing minerals appear as the primary limiting factors for soybean cultivation on acid soils. Therefore, the purpose of this research is to determine the effect of organic fertilizers and Plant Growth Promoting Rhizobacteria (PGPR) on plant growth and yield. A completely randomized block design (CRBD) factorial with three replications was employed, where the first variable involved the chicken and cow composts as well as Tithonia green fertilizer. Meanwhile, the second referred to PGPR at 0, 5, 10 and 15 ml.L-1. The results showed no interaction between the application of organic fertilizers and PGPR on soybean growth as well as the yield. Furthermore, the cow manure treatment of 10 t.ha-1 reportedly increased the total dry weight and sample growth rate by 0.44 and 0.86%, respectively, compared to the chicken manure at similar composition. Also, 10 ml.L-1 of PGPR was known to improve the pod quantity per plant and harvest index by 0.58 and 2.66% harvest index, correspondingly, than without PGPR.